How to Cohabitate. (February 2020) - Reid, Matt
Sharon Sassler and Amanda Jayne Miller set out to expand our understanding of how cohabitating relationships evolve in their compelling new book, Cohabitation Nation: Gender, Class, and the Remaking of Relationships.